Extract of Black Rice (Oryza sativa L. ‘Sembada Hitam’) Bran Protect Cytotoxicity of Hydrogen Peroxide on Vero Cells in a Short Time Incubation: Black rice bran ‘Sembada Hitam’ protect cytotoxicity of H2O2 - Aprilianti, Suci Hari; Purwestri, Yekti Asih; Saragih, Hendry T.S.S.G; Nuriliani, Ardaning (Journal of Tropical Life Science, 2024)
Oxidative stress induced by hydrogen peroxide (H2O2) can lead to cellular damage, contributing to degenerative diseases and aging. Black rice bran is a functional food known for its antioxidant properties, which are crucial in reducing the adverse effects of oxidative stress and maintaining redox balance. In this study, we aimed to investigate the protective effect of the extract of black rice bran (EBRB) 'Sembada Hitam' on Vero cells against H2O2 toxicity. To evaluate the protective effect, a co-culture method was employed, and cell viability was assessed using the MTT assay. Additionally, cell growth was examined through trypan blue staining. Vero cells were exposed to different concentrations of H2O2 and EBRB for a 24-hour period. The results demonstrated that EBRB at concentrations of 15.625, 250, and 500 μg/mL exhibited a protective effect on Vero cells exposed to H2O2 at concentrations of 100, 200, and 400 μM, respectively. Notably, when Vero cells were treated with EBRB at concentrations of 250 or 500 μg/mL for five days in conjunction with H2O2 exposure at concentrations of 200 or 400 μM for 24 hours, a significant decrease in cell viability was observed on day 3. Based on the collective findings, it can be concluded that EBRB has the potential to protect Vero cells against H2O2 -induced toxicity, but primarily during a short-term incubation period. Overall, this study highlights the protective properties of EBRB against H2O2 -induced cellular damage and emphasizes the importance of further investigations to fully elucidate the underlying mechanisms and potential long-term effects of EBRB on cell viability.